Report of the Committee on the Elimination of Racial Discrimination, Sixty-ninth Session - United Nations Department for General Assembly; Conference Management (United Nations, 2014)
This is the official record of the Report of the Committee on the Elimination of Racial Discrimination on the Eighty-third session (12–30 August 2013) and the Eighty-fourth session (3–21 February 2014)